Alcune considerazione seu procreazione e sessualità nel matrimonio canonico - Boni, Geraldina (2010)
The article illustrates how the consideration of procreation in canonical marriage has developed. After a preliminary statement about the main contribution of the Christian thought on the matter, we focus on the different concept of marriage following Vaitcan II. The Code of 1983 exceeds the contractualictis and physicistic concept of marriage of the prior Code, in which it was reduced to simple exchange between husband and wihfe, especially of "ius in copus in ordine ad actus per se aptos ad prolis generationem". On the other hand, the increased value given to spiritual and emotional aspects can not lead to a depreciation of sexuality and procreation in marriage. Marriage is deeply rootet on the sexual bipolarity of male and female and consists of the reciprocal donation of sexuality from the married couple: a potentially fertile sexuality, open to procreation as successful completion of conjugal love
Keywords: Katholische Kirche; Katholische Kirche; Ehe; Eherecht; Sexualität; Sexualethik; Kind; Recht; Geschichte; Sakramentenrecht; Eheziel; Bonum prolis; ius in corpus